CLINICAL AND LABORATORY SIGNS OF CALCIUM DEFICIENCY IN ADOLESCENTS - O.V. Osipenko; I.V. Vakhlova; E.B. Trifonova ("Paediatrician" Publishers LLC, 2009)
The article presents the results of a study of mineral metabolism in healthy children of pre- and pubertal age. Factors leading to the disorders of bone tissue mineralization and parameters of physical development of children are analyzed. Authors describe the results of study of bone remodeling and mineral density of bone tissue biochemical markers in adolescents of 10-15 years old. Key words: children, pubertal age, mineral density of bone tissue, osteopenia, sport. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):56-62)